BMI, eating habits and sleep in relation to salivary counts of mutans streptococci in children – the IDEFICS Sweden study. Issue 6 (31st July 2015) - Arvidsson, Louise; Birkhed, Dowen; Hunsberger, Monica; Lanfer, Anne; Lissner, Lauren; Mehlig, Kirsten; Mårild, Staffan; Eiben, Gabriele
Abstract: Objective: The objective of the present study was to investigate the association between salivary counts of mutans streptococci (MS) and children's weight status, while considering associated covariates. MS ferments carbohydrates from the diet and contributes to caries by lowering the pH in dental plaque. In adults, high counts of MS in saliva have been associated with overweight, but this has not been shown in children. Design: Cross-sectional study investigating salivary counts of MS, BMI Z -score, waist circumference, meal frequency, sugar propensity and sleep duration, in children. Setting: West Sweden. Subjects: Children ( n 271) aged 4–11 years. Results: Medium–high counts of MS were positively associated with higher BMI Z -score (OR=1·6; 95 % CI 1·1, 2·3). Positive associations were also found between medium–high counts of MS and more frequent meals per day (OR=1·5; 95 % CI 1·1, 2·2), greater percentage of sugar-rich foods consumed (OR=1·1; 95 % CI 1·0, 1·3) and female sex (OR=2·4; 95 % CI 1·1, 5·4). A negative association was found between medium–high counts of MS and longer sleep duration (OR=0·5; 95 % CI 0·3, 1·0). Conclusions: BMI Z -score was associated with counts of MS. Promoting adequate sleep duration and limiting the intake frequency of sugar-rich foods and beverages could provide multiple benefits in public health interventions aimed at reducing dental caries and childhood overweight.